Neural Correlates of Simulated Driving While Performing a Secondary Task: A Review - Palmiero, Massimiliano; Piccardi, Laura; Boccia, Maddalena; Baralla, Francesca; Cordellieri, Pierluigi; Sgalla, Roberto; Guidoni, Umberto; Giannini, Anna Maria (Frontiers in Psychology, 2019)
Distracted driving consists in performing a secondary task while driving, such as cell-phone conversation. Given the limited resources of the attentional system, engaging in a secondary task while driving increases the risk to have car accidents. The secondary task engagement while driving can depend on or be affected by different factors, including driver’s individual characteristics, necessities, environmental conditions, and so forthetc... In the present work, the neuroimaging studies that investigated the brain areas involved in simulated driving during the execution of a secondary task (visual and overall auditory tasks) were reviewed in light of driving settings. In general, although there are also differences in decrease and increase brain activations across studies, due to the varieties of paradigms used (simulators, secondary tasks and neuroimaging techniques), the dual-task condition (simulated driving plus secondary task), as compared to the simulated driving-alone condition, was generally found to yield a significant shift in activations from occipital to fronto-parietal brain regions. These findings show that when a secondary task is added during driving the neural system redirects attentional resources away from visual processing, increasing the possibility of incorrect, dangerous or risky behavioural responses. The shift of the attentional resources can occur, even if driving behaviour is not explicitly affected. Limits of the neuroimaging studies reviewed and future research directions, including the need to explore the role of personality factors in the modulation of the neural programs while engaging distracted driving, are briefly discussed.